Mechanism of Action of Atypical Antipsychotic Drugs in Mood Disorders - Grinchii, Daniil (Int J Mol Sci, 2020)
Atypical antipsychotic drugs were introduced in the early 1990s. Unlike typical antipsychotics, which are effective only against positive symptoms of schizophrenia, atypical antipsychotics are effective against negative and cognitive symptoms as well. Furthermore, they are effective not only in psychotic but also in affective disorders, on their own or as adjuncts to antidepressant drugs. This review presents the neural mechanisms of currently existing atypical antipsychotics and putative antipsychotics currently being investigated in preclinical and clinical studies and how these relate to their effectiveness in mood disorders such as depression, anxiety, and post-traumatic stress disorder (PTSD). Typical antipsychotics act almost exclusively on the dopamine system. Atypical drugs, however, modulate serotonin (5-HT), norepinephrine, and/or histamine neurotransmission as well. This multimodal mechanism of action putatively underlies the beneficial effect of atypical antipsychotics in mood and anxiety disorders. Interestingly, novel experimental drugs having dual antipsychotic and antidepressant therapeutic potential, such as histamine, adenosine, and trace amine-associated receptors (TAAR) ligand, are also characterized by a multimodal stimulatory effect on central 5-HT, norepinephrine, and/or histamine transmission. The multimodal stimulatory effect on central monoamine neurotransmission may be thus primarily responsible for the combined antidepressant and antipsychotic therapeutic potential of certain central nervous system (CNS) drugs.